Unlocking circular bioeconomy potential of termite-gut yeasts: dual bioremediation and biodiesel production - Ali, Sameh S.; Xiong, Min; Al-Tohamy, Rania; Jiao, Haixin; Schagerl, Michael; Kornaros, Michael; Sun, Jianzhong (Frontiers in Bioengineering and Biotechnology, 2026)
Lignin-derived aromatics and synthetic azo dyes are among the most persistent and toxic pollutants released by textile processing, petrochemical industries, pulp-and-paper manufacturing, and agricultural waste streams. Their structural complexity, chemical stability, and resistance to degradation impose substantial ecological and health concerns, highlighting the urgent need for sustainable and low-cost biological solutions. Growing evidence positions termite-gut symbioses—particularly yeast populations inhabiting wood-feeding termites—as a promising reservoir of biocatalysts capable of both degrading recalcitrant aromatic pollutants and generating lipids suitable for biodiesel production. This review synthesizes current knowledge on termite-gut-derived oleaginous yeasts, focusing on their enzymatic mechanisms, metabolic capabilities, and biotechnological potential within integrated biorefinery concepts. Recent literature reports demonstrate that termite-associated yeasts harbor diverse oxidative and reductive enzymes, including laccases, dye-decolorizing peroxidases, manganese peroxidases, dioxygenases, and azoreductases, which collectively mediate the depolymerization, detoxification, and mineralization of lignin-derived and dye-derived aromatic compounds. Pollutant-induced oxidative stress responses in oleaginous yeasts have also been widely documented to enhance lipid biosynthesis, linking environmental detoxification to biodiesel precursor generation through an energetically favorable, self-reinforcing metabolic cycle. Advances in genomics, transcriptomics, metabolic engineering, yeast surface display, and directed evolution have further expanded the opportunities to engineer multi-trait yeast chassis optimized for challenging industrial waste streams. This review also evaluates techno-environmental considerations relevant to practical deployment, including process scalability, tolerance to inhibitors, reactor configurations, and integration with lignocellulosic biorefineries and wastewater treatment systems. Particular attention is given to the potential of engineered termite-gut yeasts to function in hybrid microbial consortia, immobilized biocatalytic systems, and continuous-flow platforms. By consolidating the emerging scientific evidence, this review highlights termite-gut yeasts as a promising biological platform capable of bridging aromatic pollutant detoxification with renewable lipid production. Their dual functionality aligns strongly with circular bioeconomy goals, offering a path toward low-carbon, waste-to-value biorefineries.